Lupus New Advances and Challenges - Lionaki, Sophia (IntechOpen, 2020)
Systemic lupus erythematosus, the prototype of an autoimmune disorder, may affect several organs and may run a chronic course between relapse and remission. This book covers important aspects of the disease, including epidemiology, pathophysiology, and neuropsychiatric manifestations, including basic science and clinical features and management. In affected patients, the fundamental problem of fertility is reassessed including the risk of the disease, the possibility of fetal loss, the safety of drugs during pregnancy, and the current diagnostic and suggested therapeutic strategies of reproductive medicine. Finally, the issue of pathogenesis is revisited with a thorough description of animal models in relation to physiology and potential novel therapies.